“Attitudes to voices”: a survey exploring the factors influencing clinicians’ intention to assess distressing voices and attitudes towards working with young people who hear voices - Rammou, Aikaterini; Berry, Clio; Fowler, David; Hayward, Mark (Frontiers in Psychology, 2023)
Introduction Due to the general psychopathological vulnerability of young people who hear distressing voices, research has stressed the importance for clinicians to assess this experience in youth. Nonetheless, the limited literature on the topic comes from studies with clinicians in adult health services and it primarily reports that clinicians do not feel confident in systematically assessing voice-hearing and doubt the appropriateness of doing so. We applied the Theory of Planned Behavior and identified clinicians’ job attitudes, perceived behavioral control, and perceived subjective norms as putative predictors of their intent to assess voice-hearing in youth. Method Nine hundred and ninety-six clinicians from adult mental health services, 467 from Child and Adolescent Mental Health (CAMHS) and Early Intervention in Psychosis (EIP) services and 318 primary care clinicians across the UK completed an online survey. The survey gathered data on attitudes toward working with people who hear voices, stigmatizing beliefs, and self-perceived confidence in voice-related practices (screening for, discussing and providing psychoeducation material about voice-hearing). Responses from youth mental health clinicians were compared with professionals working in adult mental health and primary care settings. This study also aimed to identify what youth mental health clinicians believe about assessing distressing voices in adolescents and how beliefs predict assessment intention. Results Compared to other clinicians, EIP clinicians reported the most positive job attitudes toward working with young voice-hearers, the highest self-efficacy in voice-hearing practices, and similar levels of stigma. Job attitudes, perceived behavioral control and subjective norms explained a large part of the influences on clinician’s intention to assess voice-hearing across all service groups. In both CAMHS and EIP services, specific beliefs relating to the usefulness of assessing voice-hearing, and perceived social pressure from specialist mental health professionals regarding assessment practices predicted clinician intention. Discussion Clinicians’ intention to assess distressing voices in young people was moderately high, with attitudes, subjective norms and perceived behavioral control explaining a large part of its variance. Specifically in youth mental health services, promoting a working culture that encourages opening and engaging in discussions about voice-hearing between clinicians, and with young people, and introducing supportive assessment and psychoeducation material about voice-hearing could encourage conversations about voices.